Adsorption of Biogenic Amines from Synthetic and Real Wastewater using a Zwitterion‐Functionalized Blast Furnace Slag. Issue 7 (19th June 2021) - Dauda, Mohammed; Al‐Malack, Muhammad H.; Basheer, Chanbasha
Abstract: Blast furnace slag functionalized with sulfamic acid (zwitterion) shows an extraordinary potential for the removal of biogenic amines from spiked water and real wastewater samples. The functionalized slag is characterized using scanning electron microscopy‐energy dispersive spectroscopy (SEM/EDS), Fourier transform infrared spectroscopy (FTIR), and acid site density test. Its performance toward the removal of selected biogenic amines (putrescine, tyramine, and 2‐phenylethylamine) is evaluated at different experimental conditions that include pH, contact time, adsorbent dosage, and initial concentration. The central composite experimental design is employed in investigating the effect of these individual factors and their interactions. The adsorption experiment results fit both the Langmuir isotherm model and pseudo‐second‐order kinetic model based on the computed high coefficient of determination ( R 2 ) values. Maximum adsorption capacity values of 80.64 mg g −1 for 2‐phenylethylamine, 12.5 mg g −1 for putrescine, and 64.52 mg g −1 for tyramine are estimated from the Langmuir isotherm model. Hydrogen bonding interaction between the S═O groups of the functionalized slag and protonated amino groups of biogenic amines is speculated as the possible mechanism of adsorption. The prepared functionalized slag also exhibits good adsorptive removal of biogenic amines in a date palm fruit processing industrial wastewater sample. Abstract : The removal of toxic biogenic amines from wastewater with an adsorbent derived from blast furnace slag (industrial waste material) is investigated. The slag is functionalized with sulfamic acid to enhance its binding to the amines. These results show that sulfamic acid functionalized slag can serve as a potential low‐cost material for the treatment of biogenic amines contaminated water.